2004
DOI: 10.1038/modpathol.3800209
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in components of the Wnt signaling pathway in adenoid cystic carcinoma

Abstract: The Wnt signaling pathway is essential for normal development and organogenesis. However, inappropriate activation of Wnt signaling, which results in the nuclear translocation of b-catenin, is associated with the development of various types of neoplasm. In this study, we investigated possible mutations in the genes for components of this pathway, namely, CTNNB1 (the gene for b-catenin), AXIN1, and APC, in adenoid cystic carcinoma, by PCR, analysis of single-strand conformational polymorphism, and sequencing. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
42
0
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 19 publications
1
42
0
2
Order By: Relevance
“…Axin has different mutation frequencies in colon cancer (Jin et al, 2003) and bladder tumour tissue (Daa et al, 2004). In Axin gene mutations in primary HCC cells, β-catenin accumulation was found in the cytoplasm and the nucleus, and β-catenin/Tcf transcription activity was enhanced.…”
Section: Discussionmentioning
confidence: 99%
“…Axin has different mutation frequencies in colon cancer (Jin et al, 2003) and bladder tumour tissue (Daa et al, 2004). In Axin gene mutations in primary HCC cells, β-catenin accumulation was found in the cytoplasm and the nucleus, and β-catenin/Tcf transcription activity was enhanced.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of tumor RNA by microarray revealed that ACCs express genes associated with myoepithelial differentiation along with high levels of the transcription factor Sox4 18. The latter normally regulates embryonic development and is also a candidate human oncogene 19. Other overexpressed genes include casein kinase 1‐epsilon and frizzled‐7 , which are implicated in the Wnt/β‐catenin signaling pathway and in tumorigenesis.…”
Section: Introductionmentioning
confidence: 99%
“…This might be true even if no nuclear b-catenin immunoreactivity was found in the two MBs that over-expressed both FZD1 and MYC and were investigated for b-catenin positivity (samples 9 and 16 in Table 1). Indeed, it has been previously proved that negative immunohistochemical results do not eliminate the possibility of increased nuclear localization of CTNNB1-with consequent WNT/CTNNB1 pathway activation-because weak nuclear staining may be difficult to evaluate [23]. Moreover, the lack of nuclear b-catenin staining has been reported in tumors arising from WNT/ CTNNB1 pathway deregulation, and a variety of WNT/ CTNNB1 pathway target genes, such as MYC, may be upregulated even in the absence of nuclear b-catenin immunoreactivity [12,23].…”
Section: Discussionmentioning
confidence: 98%
“…Indeed, it has been previously proved that negative immunohistochemical results do not eliminate the possibility of increased nuclear localization of CTNNB1-with consequent WNT/CTNNB1 pathway activation-because weak nuclear staining may be difficult to evaluate [23]. Moreover, the lack of nuclear b-catenin staining has been reported in tumors arising from WNT/ CTNNB1 pathway deregulation, and a variety of WNT/ CTNNB1 pathway target genes, such as MYC, may be upregulated even in the absence of nuclear b-catenin immunoreactivity [12,23]. Finally, as observed by Merle et al in human hepatocellular carcinomas, over-expression of FZD receptors might lead to levels of nuclear b-catenin sufficient to induce target genes, but not strong enough to be detected by immunohistochemistry [6].…”
Section: Discussionmentioning
confidence: 98%